The Role of Religiosity and Intrafamilial Relationships in Suicidal Ideation among High-school Adolescents: A PLS-SEM Analysis - Guevara Rabanal, Diego Andre (2025)
Suicidal ideation is a critical public health concern, particularly among adolescents, where various psychosocial factors may influence its prevalence. This study examines the relationship between religiosity, intrafamilial relationships, and suicidal ideation among high school students in Metropolitan Lima, Peru. Using Partial Least Squares Structural Equation Modeling (PLS-SEM), we analyzed data collected from 339 students of one high school in Metropolitan Lima, Peru to determine how different dimensions of religiosity (subjective religiosity and religious practice) and intrafamilial relationships (positive perception and difficulties) predict positive and negative suicidal ideation. Results indicate that the perception of family unity and support significantly reduces negative suicidal ideation and enhances positive suicidal ideation, while difficulties in intrafamilial relationships contribute with enhances negative suicidal ideation and reduces positive suicidal ideation. Contrary to expectations, only subjective religiosity was found to have a positive significant impact on positive suicidal ideation, suggesting that personal religious beliefs, rather than formal religious practices, play a role in shaping adolescent mental health. These findings have implications for suicide prevention strategies, emphasizing the importance of family cohesion and the nuanced role of religiosity in adolescent well-being. Future research should explore these relationships longitudinally and incorporate qualitative insights to better understand the underlying mechanisms.